A collective case study to understand the whys and wherefores of not using technology in mathematics education - Eren, Mehmet. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
The purpose of this study was to investigate the barriers of technology integration in primary mathematics education. To determine the barriers, three different themes were used: (a) teachers’ definition of self in integration efforts, (b) the relationship between technology and pedagogy in teachers’ perspectives, and (c) teachers’ understanding of the nature of technology in today’s world. Convenience sampling method was used to select six primary mathematics teachers. A multiple case study design consisting of six distinct cases was used as the methodology. An adapted semi-structured interview was used as the instrument. To make comparisons within and across cases, results were stated under two main headings: Within case analysis and cross case analysis. The data, first of all, revealed that the access barrier to the available sources is prominent in all cases. Secondly, considering pedagogical concerns, the motivation of the students and the pace of the lessons are the points on which technology integration has the greatest impact. Professional development was another barrier participants had a consensus on. In this respect, the participants proposed a ten-stage plan to educate teachers in terms of technology integration. Lastly, but most importantly, it was proposed that technology itself in today’s world can appear as the next barrier.
Keywords: Mathematics -- Study and teaching.; Technology -- Study and teaching.